EFFECT OF WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE ORGANIZATIONAL COMMITMENT WITH JOB SATISFACTION AS INTERVENING VARIABLE (Empirical Studies at Pandanaran University) - Maria M Minarsih; Dewi Fatmasari (Jurnal Ekonomi, 2022)
This study aims to examine the effect of education, work discipline, and work environment on organizational commitment with work experience as an intervening variable. This research is a quantitative research. The data collection instrument uses a pen. Determination of respondents using the Census technique. Census is a sampling technique that takes the entire population as a sample. The population in this research is 100 employees at Pandanaran University. The sample in this study that can. Data analysis using SPSS with path analysis and Sobel test. Data collection techniques in this study used interview techniques, questionnaires and literature study. The data obtained were analyzed quantitatively using validity test, reliability test, multiple linear regression and hypothesis testing with t test, F test, coefficient of determination and path analysis. The results of this study indicate that education, work discipline, and work environment have a positive and significant effect. to organizational commitment. Furthermore, the work experience variable shows a significant and positive effect on work commitment. On the other hand, the relationship between education, work discipline, and work environment has a significant positive effect on work experience